Influence of Inclusion of Different Levels of Azolla (Azolla pinnata) Meal in the Diet on the Performance of Pratapdhan Chicks - Yadav, C.M.; Chhipa, B.G. (Indian Journal of Animal Nutrition, 2018)
Two weeks old Pratapdhan chicks (120) were selected from Krishi Vigyan Kendra, Bhilwara, Rajasthan, India and distributed randomly into four dietary treatments having three replicates of 10 birds each. Four iso-nitrogenous diets were formulated to contain Azolla meal at 0, 5, 10 and 15%, respectively in replacement ofsoybean meal and corn bran. The experiment lasted for 120 days. There was no significant difference in the weight gain of chicks. Average weekly weight gains were 94.23, 95.16, 97.86 and 93.22 g on inclusion of azolla meal at 0, 5, 10 and 15% in the diet, respectively. Feed conversion ratio improved from 3.08 in control to 2.66 in birds fed 15% azolla meal. It was concluded that azolla meal could be used up to 15% level in the diet in partial replacement of soybean meal and corn bran in Pratapdhan chicks.